2002
DOI: 10.1128/jcm.40.5.1617-1620.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ethambutol-Resistant Mycobacterium tuberculosis Strains by Multiplex Allele-Specific PCR Assay Targeting embB306 Mutations

Abstract: We describe a multiplex allele-specific (MAS)-PCR assay to detect simultaneously mutations in the first and third bases of the embB gene codon 306ATG. These mutations are known to confer ethambutol (EMB) resistance in the majority of clinical Mycobacterium tuberculosis isolates worldwide. The mutated bases are revealed depending on the presence or absence of the respective indicative fragments amplified from the embB306 wild-type allele. Initially optimized on purified DNA samples, the assay was tested on crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…EMB inhibits an arabinosyl transferase (embB) involved in cell wall biosynthesis (Takayama and Kilburn, 1989). Telenti et al (Telenti et al, 1997) (Lee et al, 2002;Sreevatsan et al, 1997c;Mokrousov et al, 2002b;Ramaswamy et al, 2000). These five mutations are associated with 70-90% of all EMB resistant isolates (Johnson et al, 2006) it was shown that genotypic analysis identified mutations at codon 306 of the embB gene rendering resistance to EMB.…”
Section: Isoniazidmentioning
confidence: 99%
“…EMB inhibits an arabinosyl transferase (embB) involved in cell wall biosynthesis (Takayama and Kilburn, 1989). Telenti et al (Telenti et al, 1997) (Lee et al, 2002;Sreevatsan et al, 1997c;Mokrousov et al, 2002b;Ramaswamy et al, 2000). These five mutations are associated with 70-90% of all EMB resistant isolates (Johnson et al, 2006) it was shown that genotypic analysis identified mutations at codon 306 of the embB gene rendering resistance to EMB.…”
Section: Isoniazidmentioning
confidence: 99%
“…At the same time, the third base of this codon (G) is associated with an HaeIII recognition site (GG1CC) and hence the HaeIII site can be altered only if a mutation occurs in the third base of embB306. To summarize, NlaIII distinguishes between the wild-type allele and any mutant allele while HaeIII permits further discrimination of the mutants, depending on the base mutated (first [A] or third [G]) (10). It should be noted that this PCR-RFLP assay design allows monitoring for possible strain contamination during isolation and culture.…”
mentioning
confidence: 99%
“…Allelic variation in embB306 was analyzed by a PCR-RFLP assay by using restriction endonucleases NlaIII and HaeIII as previously described (10). In short, any mutation in embB codon 306ATG changes the NlaIII site (CATG1).…”
mentioning
confidence: 99%
“…Ethambutol resistance is thought to occur due to mutations in embB gene of Mycobacterium tuberculosis. The most frequent mutation occurs at the 306 amino acid position (codon Met 306) in embB gene (6,7).…”
Section: Introductionmentioning
confidence: 99%